Compressive sensing based algorithms for electronic defence - Mishra, Amit Kumar; Verster, Ryno Strauss (Springer, 2017)
This book details some of the major developments in the implementation of compressive sensing in radio applications for electronic defense and warfare communication use. It provides a comprehensive background to the subject and at the same time describes some novel algorithms. It also investigates application value and performance-related parameters of compressive sensing in scenarios such as direction finding, spectrum monitoring, detection, and classification.
Keywords: Compressed sensing (Telecommunication); Electronic surveillance.; Engineering.; Computers, Special purpose.; System safety.; Electrical engineering.; elektronické knihy; electronic books